Association of adherence to lifestyle recommendations and risk of colorectal cancer: a prospective Danish cohort study - Kirkegaard, Helene (BMJ Publishing Group Ltd., 2010)
Objectives To evaluate the association between a simple lifestyle index based on the recommendations for five lifestyle factors and the incidence of colorectal cancer, and to estimate the proportion of colorectal cancer cases attributable to lack of adherence to the recommendations. Design Prospective cohort study. Setting General population of Copenhagen and Aarhus, Denmark. Participants 55 487 men and women aged 50-64 years at baseline (1993-7), not previously diagnosed with cancer. Main outcome measure Risk of colorectal cancer in relation to points achieved in the lifestyle index (based on physical activity, waist circumference, smoking, alcohol intake, and diet (dietary fibre, energy percentage from fat, red and processed meat, and fruits and vegetables)) modelled through Cox regression. Results During a median follow-up of 9.9 years, 678 men and women had colorectal cancer diagnosed. After adjustment for potential confounders, each additional point achieved on the lifestyle index, corresponding to one additional recommendation that was met, was associated with a lower risk of colorectal cancer (incidence rate ratio 0.89 (95% confidence interval 0.82 to 0.96). In this population an estimated total of 13% (95% CI 4% to 22%) of the colorectal cancer cases were attributable to lack of adherence to merely one additional recommendation among all participants except the healthiest. If all participants had followed the five recommendations 23% (9% to 37%) of the colorectal cancer cases might have been prevented. Results were similar for colon and rectal cancer, but only statistically significant for colon cancer. Conclusions Adherence to the recommendations for physical activity, waist circumference, smoking, alcohol intake, and diet may reduce colorectal cancer risk considerably, and in this population 23% of the cases might be attributable to lack of adherence to the five lifestyle recommendations. The simple structure of the lifestyle index facilitates its use in public health practice.